Aplikasi Network Analysis Metode CPM (Critical Path Method) Model AON Untuk Menentukan Penjadwalan Proyek Pembangunan Gedung Perpustakaan UIN Malang - Binti Karomah (Journal of Science and Technology, 2022)
The problem  The with development projects is to determine the project schedule so that it can be completed in an optimal (minimum) time. Scheduling with Network, among others, uses the CPM (Critical Path Method). The network diagram representation of the method is in the form of a directed graph (digraph) which is presented in two models, namely AOA (Activity On Arc) and AON (Activity On Node. Activities in the AON model are placed on nodes. This study aims to determine the application of network analysis using the CPM method. The AON model on the scheduling of the library development project at UIN Malang The methods used are forward pass, backward pass, and total slack so that it can be known the fastest or late time an activity can be started or ended and the amount the allowable delay time for an activity and its critical activities.Previous research only used the PERT (Program Evaluation and Review Technique) method and the Gantt Chart method, so in this study the author will use another method, namely the CPM Model AON method. pen time the construction project schedule is 293 days starting from 01-07-2022 to 27-05-2023. From the results of the analysis using the CPM method, it was obtained that from 298 project preparation activities, 17 activities were critical activities so that their implementation could not be delayed because it would result in a delay in project completion time.